Trends in Marketing of New Insurance Schemes and Distribution: An Empirical Study on Indian Life Insurance Sector - Chaudhury, Suman Kalyan; Das, Sanjay Kanti (Journal of Business and Technology (Dhaka), 2015)
Insurance has been an integral part of financial services system and recognised as a cornerstone of a countrys financial health and symbol of progress. Insurance provides for the financial security of citizens and their families. The present paper discusses the role of marketing in insurance distribution of life insurance sector in India as insurance offers a valuable investment advices and serves as an effective step towards both individual and national financial stability. The waves of globalisation have deeply influenced the insurance sector worldwide. Financial globalisation has been strongly supported by globalisation of insurance. With the increase in trade, direct investment and portfolio investment, there has been an ever growing demand for insurance services particularly in the emerging markets. Globalisation of insurance market, as a part of the overall process of liberalisation in emerging and other countries enabled the foreign insurance companies to enter in those countries and benefited both. Triggered by the sound fundamentals in global economy and internationalisation of world markets, several countries turned towards free market regimes in banking and insurance, putting an end to several decadeold state-owned controlled markets. There was a remarkable progress in the Indian insurance industry soon after the acceptance and adaptation of LPG in the year 1991. After 1991, the Indian life insurance industry has geared up in all respects, as well as it has been forced to face a lot of healthy competition from many national as well as international private insurance players. It is also reported by Swiss Re and Munich Re that there would be 20-25 percent growth in life and health insurance market by 2015, particularly in India and China. In this paper an effort is made to study the current status and challenges faced by the life insurance business houses in India. Journal of Business and Technology (Dhaka) Vol.9(2) 2014; 61-81